Envelhecimento e relações sociais: um estudo com pacientes psicóticos - Freitas, Ana Paula de (2006)
This study aimed at investigating how the elderly with psychotic disorders of precocious beginning has aged from the social relations point of view. An interview was carried out in order to obtain sociodemographic data from the subjects, in number of 16 nine female and seven male, all of them retired, resident in the city of Uberlândia MG, between 57 and 79 year-old ages. Most of the sample (75%) has undergone psychiatric hospitalizations at least once during their disease period. Three types of information were categorized: the terms used by the subjects to refer to their psychiatric disorders; the different familiar arrangements; the subjects social activities. The subjects have been asked to describe their present social relations networks as well as the ones from the period before the beginning of the disorder, and for that, the Social Convoy diagram has been used. In the analysis of the present diagrams, it was observed an average of (17,12) people per convoy, superior to other previous studies. The convoys from the period before the beginning of the disorder had an average of nine people mentioned, a little more of the half of the present convoys. The size of the convoys was not related to the fact of the subjects having generated a family of their own, neither to their age nor to the number of hospitalizations or the duration of the disorders. The nuclear family has been the most mentioned in the present convoys inner circles, as well as in the old ones; the extended family has been the most mentioned in the other two circles of the present convoys, while in the convoys from the period before the beginning of the disorder friends have been the most mentioned. Women have mentioned other women in their convoys more frequently, but it has not happened to the men s group. The quality of the established relations seems to be damaged when one considers frequency, type of contact and social support. Therefore, there are reported social expansiveness increased, but low affection expansiveness. All the subjects have reported satisfaction with their social convoys. The qualitative analysis has been based on the Social-Emotional Selectivity Theory and on the Sociometry.